The Impact of JAK2 V617F, CALR, and MPL Mutations as Molecular Diagnostic Markers of Myeloproliferative Neoplasms in Kurdish Patients. A Single-center Experience: JAK2 V617F, CALR and MPL mutations as molecular diagnostic markers - Basim Najm, Maysam; Jalal, Sana Dlawar; Getta, Hisham Arif (Cellular and Molecular Biology, 2022)
Myeloproliferative neoplasms have a high prevalence and genetic mutations play a role in their occurrence. Determination of these mutations can be valuable in the screening, diagnosis, and treatment of patients. Therefore, this study was conducted to investigate the mutation of JAK2, CALR, and MPL genes as diagnostic and prognostic biomarkers in patients with myeloproliferative neoplasms in the Kurdistan region of Iraq. This case-control study was conducted in 2021 on 223 patients with myeloproliferative neoplasm referred to Hiwa Sulaymaniyah Cancer Hospital. The data were collected from three groups of Polycythemia Vera (PV) patients (70 people), Essential Thrombocythemia (ET) (50 people), and Primary Myelofibrosis (PMF) (103 people) by sampling for JAK2, CALR, and MPL gene mutation tests and demographic and clinical information have been collected through examination. The data were analyzed by SPSS v. 23 software and descriptive and chi-square statistical tests. The study included 223myeloproliferative neoplasms (MPN) patients. JAK2 V617F mutation was detected mostly in PV patients and CALR and MPL mutations in ET and PMF patients and this mutation difference was significant in prognosis and disease diagnosis. An association between JAK 2 mutation and splenomegaly was also demonstrated. Considering the lack of a definitive diagnostic method in myeloproliferative disease, the results of this study showed that molecular studies, including JAK2 V617F, CALR, and MPL mutations and other hematological tests can be useful and effective in the diagnosis of MPN. In addition, it is necessary to pay attention to new diagnostic methods.